1989
DOI: 10.1210/endo-125-6-2888
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pattern of Estrogen Receptor Expression in Female Mouse Genital Tracts

Abstract: The distribution of the estrogen receptor (ER) was investigated in neonatal female genital tracts (uterus, oviduct, cervix, and vagina) from days 1-22 after birth, using immunohistochemistry employing an anti-ER monoclonal antibody. In uteri, the ER in epithelial cells began to be observed by day 4. The number of positive epithelial cells and the staining intensity gradually increased until day 22 of age. On the other hand, uterine stroma cells gave a strong ER immunostaining even on day 1. The staining intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
50
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 25 publications
12
50
2
Order By: Relevance
“…Since the ER mRNA probe used in this study was picked from the A/B domain, it was expected to detect both ER 1 and 2 isoforms, which chiefly differ in the ligand domain (Patersson et al 1998). The present data was consistent with the results of several earlier studies which studied ER distribution by immunohistochemistry using perinatal tissues of mice (Yamashita et al 1989, Greco et al 1991, Jefferson et al 2000 and rats (Sar & Welsch 1999), binding assay using postnatal rats (Clark & Gorski 1972) and in situ hybridization for ER using postnatal rats (Fishman et al 1996). There are, however, a few discrepancies between our findings and some immunohistochemical reports.…”
Section: Discussionsupporting
confidence: 93%
“…Since the ER mRNA probe used in this study was picked from the A/B domain, it was expected to detect both ER 1 and 2 isoforms, which chiefly differ in the ligand domain (Patersson et al 1998). The present data was consistent with the results of several earlier studies which studied ER distribution by immunohistochemistry using perinatal tissues of mice (Yamashita et al 1989, Greco et al 1991, Jefferson et al 2000 and rats (Sar & Welsch 1999), binding assay using postnatal rats (Clark & Gorski 1972) and in situ hybridization for ER using postnatal rats (Fishman et al 1996). There are, however, a few discrepancies between our findings and some immunohistochemical reports.…”
Section: Discussionsupporting
confidence: 93%
“…The ontogeny of ERa in the female genital tract of vehicle-treated control mice was basically the same as the previous results examined with H-222 monoclonal antibody in untreated normal mice [37,39]. The present study demonstrated that DES-treatment up-regulates the expression of ERa in the epithelial cells in the oviducts, uteri, cervices and vaginae, and down-regulates the expression in the stromal cells at least until 10 days of age.…”
Section: Discussionsupporting
confidence: 90%
“…or normal rabbit IgG were used as the primary antibodies. Some sections were incubated with anti-ER rat monoclonal antibody (Abbott Laboratories, Abbot Park, IL) to compare with the previous our results concerning ontogenic ERa expression which were obtained from mice without any treatment [37]. After washing with PBS, they were then treated with anti-rabbit Ig, horseradish peroxidase (HRP) linked F(ab') 2 fragments or rat Ig, HRP linked F(ab') 2 fragments (Amersham Life Sci., UK), each 100-fold diluted with the blocking solution, for 90 min at room temperature.…”
Section: Localization Of Eramentioning
confidence: 99%
See 2 more Smart Citations